Strategic Delegation and the Shape of Market Competition - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
Which shape market competition is likely to exhibit? This question is addressed in the present paper, where firms can choose whether to act as quantity or price setters, whether to move early or delay as long as possible at the market stage and finally whether to be entrepreneurial or managerial. Moreover, firms can endogenously determine the sequence of such decisions. It is shown that in correspondence of the (unique) subgame perfect equilibrium of the game, all firms first decide to delay, then to act as Cournot competitors, and finally stockholders decide to delegate control to managers. Hence, sequential play between either managerial or entrepreneurial firms, as well as simultaneous play between entrepreneurial firms are ruled out.
Keywords: 330